2006
DOI: 10.1176/ajp.2006.163.12.2189
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo 1 H-Magnetic Resonance Spectroscopy Study of Amygdala-Hippocampal and Parietal Regions in Autism

Abstract: Abnormalities in glutamate/glutamine may partially underpin the pathophysiology of autistic spectrum disorders, and the authors confirm earlier reports that limbic areas are metabolically aberrant in these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
134
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(152 citation statements)
references
References 12 publications
16
134
2
Order By: Relevance
“…However, other studies have found decreased glutamate/Glx in ASD in regions including the ACC (Bernardi et al, 2011;van Elst, Maier, Fangmeier, & Endres, 2014) the basal ganglia (Horder et al, 2013); frontal and occipital cortex, the cerebellum (Devito et al, 2007) and white matter (Corrigan et al, 2013). Yet other studies have found no significant differences in glutamate / Glx levels between individuals with and without ASD in several different brain regions including parietal lobes (Horder et al, 2013;Page et al, 2006), frontal lobes (Horder et al, 2013) temporal lobes (Devito et al, 2007), and occipital lobes (Robertson, Ratai, & Kanwisher, 2015); the thalamus (Bernardi et al, 2011;Doyle-Thomas et al, 2014;Hardan et al, 2008); hippocampus (Joshi et al, 2012);and cerebellum (van Elst et al, 2014). Therefore, the literature regarding glutamate/Glx levels in ASD is mixed.…”
Section: Glutamate / Glxmentioning
confidence: 96%
“…However, other studies have found decreased glutamate/Glx in ASD in regions including the ACC (Bernardi et al, 2011;van Elst, Maier, Fangmeier, & Endres, 2014) the basal ganglia (Horder et al, 2013); frontal and occipital cortex, the cerebellum (Devito et al, 2007) and white matter (Corrigan et al, 2013). Yet other studies have found no significant differences in glutamate / Glx levels between individuals with and without ASD in several different brain regions including parietal lobes (Horder et al, 2013;Page et al, 2006), frontal lobes (Horder et al, 2013) temporal lobes (Devito et al, 2007), and occipital lobes (Robertson, Ratai, & Kanwisher, 2015); the thalamus (Bernardi et al, 2011;Doyle-Thomas et al, 2014;Hardan et al, 2008); hippocampus (Joshi et al, 2012);and cerebellum (van Elst et al, 2014). Therefore, the literature regarding glutamate/Glx levels in ASD is mixed.…”
Section: Glutamate / Glxmentioning
confidence: 96%
“…However, inconsistent results have been reported. For example, other studies did not find abnormally reduced levels of NAA in the frontal gray matter (Chugani et al, 1999;Levitt et al, 2003;Otsuka et al, 1999), temporal lobes (Levitt et al, 2003), bilateral thalamus (Levitt et al, 2003) and the amygdala-hippocampal and parietal regions (Page et al, 2006) in autism. These inconsistencies are difficult to interpret because studies differ widely in age range and level of functioning of their participants, and technical methodology.…”
Section: Introductionmentioning
confidence: 91%
“…In particular, the reduced size of the hippocampus and amygdala observed in autism [5,71] might be associated with deficiencies in the glutamatergic neuronal projections that originate in these regions. Abnormal concentrations of glutamine/glutamate in the amygdala and hippocampus have been reported in adults diagnosed with autism spectrum disorders, in comparison to healthy subjects [55]. Changes in glutamatergic neurotransmission might also be relevant to the abnormal synaptic function found in many genetic mouse models for autism and related syndromes [4,29,30,42,84].…”
Section: Introductionmentioning
confidence: 99%